Severe Early-onset Ovarian Hyperstimulation Syndrome with Isolated Pleural Effusion following Agonist Trigger in Gonadotropin-releasing Hormone Antagonist Cycle: A Case Report - Pooja Dhir Bhayana; Priyanka Singh; Shruti Passan (Journal of Human Reproductive Sciences)
The use of gonadotrophin-releasing hormone (GnRH) agonist trigger in GnRH antagonist cycles in in vitro fertilisation (IVF) with elective freeze-all strategy is known to practically eliminate the risk of severe ovarian hyperstimulation syndrome (OHSS). Still, there are few case reports of early-onset severe OHSS development after agonist use for final oocyte maturation. This patient presented in an emergency on post-Ovum pickup (OPU) day 5 with complaints of cough with chest pain. Her ultrasound chest revealed bilateral massive pleural effusion right > left and required pleural tap on day 7 post-OPU. On Ultrasound abdomen, she was found to have B/L enlarged ovaries consistent with post-OPU status with minimal ascites. She was managed conservatively and discharged in stable condition. This case report emphasises that severe OHSS can develop even after agonist trigger with the segmentation of IVF. The best strategy to prevent OHSS is to keep the stimulation to lower side in patients at risk and take all due precautions to prevent the same.